Autism, ADHD and parent-reported behavioural difficulties in young children with epilepsy. (October 2019) - Reilly, Colin; Atkinson, Patricia; Memon, Ayesha; Jones, Chloe; Dabydeen, Lyvia; Helen Cross, J.; Das, Krishna B.; Gillberg, Christopher; Neville, Brian G.R.; Scott, Rod C.
Highlights: 76% of children with epilepsy were in the at-risk range on a measure of behaviour. Children frequently had difficulties across multiple behavioural domains. Parents of children with epilepsy had more concerns about attention and mood. Epilepsy factors not associated with the parent reported behavioural concerns. Abstract: Purpose: To provide data on the prevalence of Autism Spectrum Disorder (ASD), Attention-Deficit/Hyperactivity Disorder (ADHD), and parent reported behaviour difficulties in young children with epilepsy, and to compare results with children with neurodisability (neurodevelopmental/neurological difficulties) without epilepsy. Method: Children with epilepsy (1–7 years, n = 48) and children with neurodisability (1–7 years, n = 48) matched for gender, chronological and developmental age underwent psychological assessment. Parents completed measures of behaviour including the Strengths and Difficulties Questionnaire (SDQ). DSM-5 diagnoses of ASD and ADHD were made at consensus case conferences. Factors associated with child behaviour were analysed using linear regression. Results: Of the children with epilepsy, 18% met ASD criteria and 40% met ADHD criteria (corresponding figures in the non-epilepsy group were 41% and 27%). A large proportion (76%–78%) in both groups scored in the at-risk range on the SDQ and frequently had difficulties across multiple behavioural domains. Children with epilepsy had more concerns expressed regarding attention and mood. None of the epilepsy factors were significantly associated with scores on the behavioural measures. Significance: Young children with epilepsy had a very high level of parent reported behavioural difficulties and a high risk for ADHD and ASD highlighting the need for comprehensive multidisciplinary assessment. Behavioural concerns were not greater than for other children with non-epilepsy related neurodisability with the exception of attention and mood. Epilepsy related factors were not associated with child behaviour, suggesting that seizures per se do not confer a unique risk for behavioural difficulties.